High-resolution X-ray absorption spectroscopy of iron carbonyl complexes1. Issue 21 (7th June 2015) - Atkins, Andrew J.; Bauer, Matthias; Jacob, Christoph R.
<x xml:space="preserve">Abstract</x> We apply high-energy-resolution fluorescence-detected (HERFD) X-ray absorption near-edge structure (XANES) spectroscopy to study iron carbonyl complexes.